2017
DOI: 10.1080/20009666.2017.1309339
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the ascending colon: two cases

Abstract: Squamous cell carcinoma (SCC) of the colon without known primary source is a rare finding that needs aggressive management. We report two cases of SCC of the colon without any clear extra-colonic source despite extensive workup. In our experience, the clinical course and prognosis are largely dependent on the presence of metastatic disease at diagnosis. The main treatment is surgery, with chemotherapy having less defined role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…SCC has an occurrence of 0.1-0.25% of cases of colorectal carcinoma [4]. SCC of the colon has less than 100 cases reported in the literature [5]. The pathogenesis of SCC is unclear, and a commonly reported theory suggests that multipotent cells differentiate into squamous cells from mucosal injury [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCC has an occurrence of 0.1-0.25% of cases of colorectal carcinoma [4]. SCC of the colon has less than 100 cases reported in the literature [5]. The pathogenesis of SCC is unclear, and a commonly reported theory suggests that multipotent cells differentiate into squamous cells from mucosal injury [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…SCC of the colon has less than 100 cases reported in the literature [5]. The pathogenesis of SCC is unclear, and a commonly reported theory suggests that multipotent cells differentiate into squamous cells from mucosal injury [2,5]. SCC has been seen more commonly in the colon as “pure” squamous cells [6], but rarely is SCC seen as mixed with another epithelium carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several predisposing conditions have been identified which create a favourable micro-environment that promotes the spread of the infection. 6 Malignancy, including occult colorectal malignancy, has been identified as a comorbid condition, and has been associated with higher death rate. 7 Although occult colorectal carcinoma has been documented several times as an aetiology, ileocecal carcinoma has never been as far as our literature search.…”
Section: Undiagnosed Metastatic Ileocecal Carcinoma: a Rare Aetiologymentioning
confidence: 99%
“…Neisseria gonorrhoeae and Chlamydia trachomatis are major causes of PID; other organisms of Enterobacteriaceae, such as E. coli, are often isolated from individuals with TOA. 6 Escherichia coli infection may result in gas formation for a TOA patient with diabetes. 4 Although the patient in the current case did not have diabetes, this result, in which E. coli was isolated, did not contradict TOA.…”
Section: Pneumoperitoneum Due To Ruptured Tubo-ovarian Abscessmentioning
confidence: 99%
“…A primary SCC of the bowel is very uncommon. Less than 0.25% of all colon carcinomas are of SCC origin 6 . The initial histological specimen showed that the SCC was originating from the fistulous tract rather than the bowel mucosa also makes this less likely.…”
Section: Figurementioning
confidence: 99%